Factors that influences on the awareness of halal food among muslim students in UNIMAP, Perlis - Nur Azwa, Kamal (2019)
The main objective of this research is to examine the factors that influences on the awareness of halal food in Malaysia especially by University students. The research examines on three factors that affecting on the awareness of halal food among Muslim students in UniMAP which are religious belief, attitude, and role of logo. Data were collected from 365 students in University Malaysia Perlis. The internal consistency reliability test of Cronbach’s Alpha indicated that all scale items were proven reliable. Inferential analysis and Multiple Regression were used in this study. The results showed that there are significant relationships between the awareness of halal food. The result also showed religious belief is the most influential factor in affecting on the awareness of halal food among Muslim student in UniMAP.